Activation of Natural Killer cells during microbial infections - Horowitz, Amir; Stegmann, Kerstin; Riley, Eleanor M. (Frontiers in Immunology, 2012)
Natural killer (NK) cells are large granular lymphocytes that express a diverse array of germline encoded inhibitory and activating receptors for MHC Class I and Class I-like molecules, classical co-stimulatory ligands and cytokines. The ability of NK cells to be very rapidly activated by inflammatory cytokines, to secrete effector cytokines and to kill infected or stressed host cells, suggests that they may be among the very early responders during infection. Recent studies have also identified a small number of pathogen-derived ligands that can bind to NK cell surface receptors and directly induce their activation. Here we review recent studies that have begun to elucidate the various pathways by which viral, bacterial and parasite pathogens activate NK cells. We also consider two emerging themes of NK cell-pathogen interactions, namely their contribution to adaptive immune responses and their potential to take on regulatory and immunomodulatory functions.